10th anniversary of the Department of dentistry of the Institute of post graduate education of Bogomolets National Medical University - Reshetnyk, Л. Л.; Proshchenko, А. М.; Stoliar, В. Г.; Volynets, В. М. (Actual Dentistry, 2024)
Summary. This paper highlights the history of the Department of Stomatology of the Institute of Postgraduate Education of Bogomolets National Medical University for the 10th anniversary of its foundation, its achievements, and prospects for development.